Soil mechanics and foundations - Budhu, M (Wiley, 2011)
Discover the Principles that Support the Practice Combining multimedia, realistic situations, clear explanations, and practical examples, Budhu's Second Edition of Soil Mechanics and Foundations helps you quickly master the key principles behind the practice of soil mechanics. Using language that is easy to understand, the text explains key concepts and principles in the context of basic mechanics, physics, and mathematics. Many worked-out examples illustrate problem-solving techniques step by step. You'll have many unique opportunities for interactive exploration, as you learn the fundamentals of soil mechanics, including: * How to characterize and classify soils * How to plan and conduct a soil investigation * The role of effective stresses, consolidation, shear strength, and critical state soil mechanics linking consolidation and shear strength * The effects of seepage on stability * How to estimate bearing capacity and settlement * How to analyze and design simple geotechnical systems Now revised, this Second Edition features a new chapter on basic geology, more examples and problems, shorter chapters, and a stronger integration with the resources on the accompanying CD. Users can follow different learning pathways depending on the educational goals. Multimedia resources provide a hands-on learning environment The CD packaged with this textbook includes: * Virtual soils laboratory * Interactive animations of basic concepts * Interactive problem solving * Interactive step-by-step examples * Electronic quizzes * Computer programs.